Improved least mean square algorithm based in satellite multi-beamforming - Yu-meng ZHANG; Ming-chuan YANG; Xiao-feng LIU; Zhong-zhao ZHANG (Tongxin xuebao)
High-throughput satellites use multi-beam technology to achieve polarization isolation and spatial isolation to reuse frequency resources,resulting in increased traffic capacity,but this presents a higher demand for fast adaptive beamforming algorithms.In order to solve the shortcoming that the convergence rate and steady-state error can not be satisfied simultaneously when using the LMS algorithm,an improved least mean square algorithm was proposed,which used the statistical average gradient update to solve the problem of the formation of beam instability caused by the instantaneous gradient,which can speed up at the beginning of the beamforming and maintain a small error value after the convergence has reached a steady state.The use of 61-element hexagonal array phased array antenna to form a 7-point beam in an environment where high-throughput satellites have a strong rainfall attenuation was considered.The results show that the improved algorithm can greatly improve the convergence speed and obtain better steady state performance under the condition of only a small increase in complexity,which can be applied to high-throughput satellite beamforming technology with severe inter-beam co-channel interference in emergency communication scenarios.